(untitled) (Al-Academy, 2025)
The researcher’s study contained four chapters. The first chapter included the research problem, its importance, and the aim of his research, which was (revealing the skills of melancholic comedy performance in the Iraqi theatre), then the researcher defined and set limits for his study, objective, spatial, and temporal. As for the second chapter, the theoretical framework, the researcher divided it into two sections according to the theoretical foundation, and it was as follows: The first topic: the emergence and development of acting performance, the second topic: comedy performance (black comedy), and the third chapter contained the research methodology, the research community, and the research sample, which was an intentional sample represented by a model One for analysis is: the play (The Hour of Blackness). After analysing the performance according to the indicators of the theoretical framework, the researcher reached a set of results and conclusions, then the researcher came out with a set of recommendations and proposals, then included the list of sources and finally the title and summary of the research in English